STREET THEATRE - THE THIRD THEATRE: AGENTS FOR SOCIAL ENGINEERING IN INDIA - Shrimati Das; Asha N. Rabb (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
Street Theatre in India, referred to as the 'Third Theatre' as a form of social and cultural communication, is deeply rooted in the Indian tradition. Many complex social issues be it gender related, child labor, imparting knowledge about HIV and AIDS, the need to educate a girl child, social and political systems, dynastic politics, are all enacted through the genre of 'street plays'. There is a'stage discussion' through varying perspectives of a number of characters, bringing an 'immediacy and urgency' to the theme under consideration. It is a situation, where the audience has not come prepared to watch a play, may not have time on hand, hence the impact of a 'street play' is direct, close, intimate and effective. The impact is 'immediate'. A 'convince-convert' strategy is employedaccompanied by a 'Dholak' (Indian percussion musical instrument) or a 'choir' to attract the crowd at the cross roads or any street corner.Keywords: Street Theatre, revolutionary, proscenium, complex social issues, stage discussion, revitalizing theatre using 'bhasha', instrument for immediate impact